The Role of School Leadership in Enhancing Teacher Well-being and Its Impact on Classroom Climate: A Case Study in a Private School in Dubai - YAHIA MOHAMMAD AL- KAWALDEH, AREEJ (2025)
This study was designed to explore how school leadership influences teacher well-being and classroom climate in a private school in Dubai. Employing an explanatory sequential mixed-methods design, the research began with a teacher survey followed by interviews with school leaders. Findings revealed that emotionally intelligent leadership, characterised by trust, recognition, and flexibility in workload management, positively impacts teacher well-being. However, barriers such as inconsistency in implementation and lack of institutional support were also noted. The results also show a strong connection between teacher well-being and classroom climate, as teachers who felt supported reported higher professional engagement and emotional responsiveness, contributing to a more positive learning environment. This study is grounded in Transformational Leadership Theory and the Job Demands-Resources Model, and it contributes to the limited body of research on leadership strategies and teacher well-being in Dubai’s private school sector. Given its complex context, marked by curriculum diversity, inspection demands, and multicultural staffing, the study offers insights to inform leadership practices across the UAE. It advocates embedding emotional support into leadership routines, empowering teachers in decision-making, and protecting time for planning and reflection. Emotionally supportive and structurally responsive leadership is essential to sustaining teacher well-being in high-demand settings. Keywords: teacher well-being, school leadership, classroom climate